THE PERCEPTION OF ROMANIA AS A WINE PRODUCING COUNTRY – A PERSPECTIVE OF INTERNATIONAL WINE SPECIALISTS - Daniel Marian MICU; Georgiana Armenița ARGHIROIU; Silviu BECIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
On an increasingly competitive world wine market, faced with the decrease in consumption, the orientation of consumers (especially younger ones) towards other types of drinks and overproduction, the battle between the wine producing countries is more intense than ever. The vast majority of these countries have understood the need to support their wine-producing industries, and this support is manifested at all levels, including development and implementation of strategic, marketing and sectoral branding programs. A common element of these efforts is the need for differentiation, both at the offer and communication level. This differentiation (necessary at the industry, producer and brand level) has the role of improving or changing the perception of consumers towards a certain product, producer or even the country of origin and giving them reasons to purchase the respective product. In order to be successful, Romania and its wine-producing industry must rally behind this quasi-generalized approach. Starting from the premise that any strategic differentiation effort at the marketing and branding level must be preceded by an accurate understanding of the existing situation, the purpose of this paper based on qualitative research, is to support the evaluation of the current situation by identifying the perception of foreign wine specialists regarding Romania as a wine-producing country. This perception was investigated on several levels, such as those related to awareness, image, attributes, benefits and attitudes associated with Romania as a wine-producing country. The main results indicated that Romania ranks in the top 3 of Eastern Europe in terms of aided awareness as a wine-producing country, but there is low recognition of its indigenous grape varieties, with 70.4% of respondents unfamiliar with them. The study also found that perceptions of Romanian wine’s attributes, such as price and quality, are unclear, with a notable portion of respondents undecided, so Romania requires a strong branding strategy to boost its international market presence and to enhance the perceived value of its wine products.